Quantification of Inter-Limb Symmetries With Rate of Force Development and Relaxation Scaling Factor - Smajla, Darjan; Žitnik, Jure; Šarabon, Nejc (Frontiers in Physiology, 2021)
The inter-limb (a)symmetries have been most often assessed with the tests that quantify the maximal muscle capacity. However, the rapid force production and relaxation during submaximal tasks is equally important for successful sports performance. This can be evaluated with an established rate of force development and relaxation scaling factor (RFD-SF/RFR-SF). The aims of our study were: 1) to assess the intra-session reliability of shortened RFD-SF/RFR-SF protocol and its absolute and symmetry outcome measures, 2) to compare the main absolute RFD-SF/RFR-SF outcome measures (slopes of RFD-SF and RFR-SF: kRTD-SF and kRFR-SF, theoretical peak RFD/RFR: TPRFD and TPRFR) across gender and sports groups, 3) to compare inter-limb symmetries across gender and sports groups for main outcome measures (kRFD-SF, kRFR-SF, TPRFD, TPRFR). A cross-sectional study was conducted on a group of young health participants (basketball and tennis players, students): 30 in the reliability study and 248 in the comparison study. Our results showed good to excellent relative and excellent absolute reliability for the selected absolute and symmetry outcome measures (kRFD-SF, kRFR-SF, TPRFD, TPRFR). We found significantly higher absolute values for kRFD-SF and TPRFD in males compared to females for the preferred (kRFD-SF: 9.1 ± 0.9 /s vs 8.6 ± 0.9 /s;) and the non-preferred leg (kRFD-SF : 9.1 ± 0.9/s vs 8.5 ± 0.8/s), while there was no effect of sport. Significantly lower symmetry values for kRFR-SF (88.4 ± 8.6% vs 90.4 ± 8.0%) and TPRFR (90.9 ± 6.8% vs 92.5 ± 6.0%) were found in males compared to females. Moreover, tennis players had significantly higher symmetry values for kRFR-SF (91.1 ± 7.7%) and TPRFR (93.1 ± 6.0%,) compared to basketball players (kRFR-SF: 88.4 ± 8.7%, TPRFR: 90.9 ± 6.7%) and students (kRFR-SF: 87.6 ± 8.7%, TPRFR: 90.5 ± 6.7%). Our results suggest that the reduced RFD-SF/RFR-SF protocol is a valuable and useful tool for inter-limb (a)symmetry evaluation. Differences in symmetry values in kRFR-SF and TPRFR (relaxation phase) were found between different sports groups. These may be explained by different mechanisms underlying the muscle contraction and relaxation. We suggest that muscle contraction and relaxation should be assessed for in-depth inter-limb symmetry investigation.